Boreal tree-rings are influenced by temperature up to two years prior to their formation: a trade-off between growth and reproduction? - Jan Tumajer; Jiří Lehejček (Environmental Research Letters, 2019)
Large spatial and between-tree variability has recently been observed in the response of boreal forests to ongoing climate change, spanning from growth stimulation by increasing temperatures to drought limitation. To predict future responses of boreal forests, it is necessary to disentangle the drivers modulating the temperature-growth interaction. To address this issue, we established two inventory plots (at a treeline and closed-canopy forest) and assembled site chronologies in Picea glauca stands at the transition between boreal forest and tundra in Northern Quebec, Canada. In addition to site chronologies, we established a set of chronologies containing, for each year, exclusive subsets of tree-rings with specific cambial age (young/old), tree dimensions (small/large) and tree social status (dominant/suppressed). All chronologies were correlated with climatic data to identify the course of climatic conditions driving variability in tree-ring widths. Our results show that the growth of P. glauca correlates significantly with summer temperature in tree-ring formation years and during up to two prior summers. Tree-ring width is positively influenced by summer temperatures in tree-ring formation year and two years prior to tree-ring formation. In addition, climate-growth correlations indicate a negative effect of summer temperature one year before tree-ring formation at the closed-canopy forest site. The pattern of climate-growth correlations is tightly synchronized with previously published patterns of climate-reproduction correlations of P. glauca , suggesting a growth-reproduction trade-off as a possible factor modulating the response of boreal forests to summer temperatures. Climatic signal does not differ between pairs of chronologies based on subsets of cambial ages, stem dimensions or tree competition status at the treeline site. However, the response to summer temperatures one year before tree-ring formation is significant only in mature (old, large and dominant) individuals at the closed-canopy site. The inverse pattern of temperature-growth correlations during a sequence of three years challenges predictions of how boreal forests respond to climate change.